Anxiety and posttraumatic stress in post-acute sequelae of COVID-19: prevalence, characteristics, comorbidity, and clinical correlates - Ferrando, Stephen J.; Lynch, Sean; Ferrando, Nicole; Dornbush, Rhea; Shahar, Sivan; Klepacz, Lidia (Frontiers in Psychiatry, 2023)
Background: Anxiety and Post traumatic stress symptoms have been reported in association with acute and post-acute sequelae of COVID-19 (PASC). Purpose: This study aimed to determine the cross-sectional prevalence, characteristics and predictors of clinically significant anxiety and post-traumatic stress in a study of neuropsychiatric sequela of PASC. Method: 75 participants recruited from a post-COVID-19 recovery program and the community were assessed for sociodemographic, medical, psychiatric and neurocognitive symptoms and performance. The generalized anxiety questionnaire-7 (GAD-7) and post-traumatic stress disorder questionnaire for DSM5 (PCL5) were utilized to measure anxiety and PTSD symptoms. Cutoff scores were utilized to determine levels of clinically significant generalized anxiety and PTSD. Results: The cohort was 71% female, 36% ethnic minority, with the main age of 43.5 years, 80% employment, 40% with the prior psychiatric treatment history and 2/3 seeking post-COVID care for PASC. Clinically significant generalized anxiety was found in 31% and PTSD was found in 24% of the cohort. Nervousness and excessive worry were the most prominent GAD symptoms, while changes in mood/cognition and avoidance were most frequent in PTSD. There was a high degree of comorbidity between clinically significant anxiety, PTSD, depression and fatigue. In logistic regression, acute COVID illness severity, fatigue and prior psychiatric history predicted clinically significant anxiety and PTSD. Conclusion: Clinically significant generalized anxiety and PTSD are found in a substantial proportion of individuals after COVID-19 infection. They are highly comorbid with each other as well as with depression and fatigue. Severity of acute COVID illness, prior psychiatric history and fatigue appear to be important clinical predictors. Taken together, these data support aggressive screening and treatment for undetected anxiety, PTSD, depression and fatigue after acute COVID-19.